Macitentan in Pulmonary Arterial Hypertension: A Focus on Combination Therapy in the SERAPHIN Trial - Jansa, Pavel; Pulido, Tomás (American journal of cardiovascular drugs, 2018)
UNLABELLED: SERAPHIN was a double-blind, placebo-controlled, event-driven phase III trial that evaluated the effects of long-term treatment with macitentan, an oral endothelin receptor antagonist, in patients with pulmonary arterial hypertension (PAH). The majority of patients were receiving PAH therapy at enrollment, providing the opportunity to evaluate the efficacy and safety of macitentan in combination with other PAH therapies (predominantly phosphodiesterase type 5 inhibitors [PDE-5i]). In patients receiving background therapy, macitentan reduced the risk of morbidity/mortality by 38% compared with placebo (hazard ratio [HR] 0.62; 95% confidence level [CL] 0.43-0.89; p = 0.009). Furthermore, patients receiving macitentan and background therapy had a 37% reduction in the risk of being hospitalized for PAH (HR 0.63; 95% CL 0.41-0.96) compared with patients receiving background therapy only (placebo arm). Macitentan treatment in combination with background therapy was also associated with improvements in exercise capacity, functional class, cardiopulmonary hemodynamics, and health-related quality of life compared with background therapy alone. The safety profile of macitentan as part of a combination therapy regimen was consistent with that of macitentan in the overall SERAPHIN population. The SERAPHIN study has provided evidence that combination therapy with macitentan and a PDE-5i is effective and well tolerated in the management of PAH. Based on these data, and those from subsequent long-term trials, combination therapy is increasingly recognized as an important treatment option for improving long-term outcomes in PAH. CLINICAL TRIAL REGISTRATION NUMBER: NCT00660179.
Keywords: Endothelin Receptor Antagonists; antagonisté endotelinového receptoru; sulfonamidy; inhibitory fosfodiesterasy 5; plicní hypertenze; Humans; Hypertension, Pulmonary; Pyrimidines; lidé; dvojitá slepá metoda; kombinovaná farmakoterapie; pyrimidiny; Clinical Trials, Phase III as Topic; Phosphodiesterase 5 Inhibitors; Sulfonamides; klinické zkoušky, fáze III jako téma; Drug Therapy, Combination; Double-Blind Method